Acceleration of the Banking Sector and Economic Growth: Effectiveness of Economic Recovery Strategies Post-Covid-19 - Nugroho, Muh Rudi; Rokhaniyah, Siti (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2024)
The banking sector around the world is under great pressure due to the current state of the Covid-19. This study investigates how Covid-19 impacts systemic risk in the banking sector across all types of banking lines affected by Covid-19. This study found that all banking lines experienced a significant increase in systemic risk among the types of banking that were sampled initially. By using spillover policies, it is also possible to identify institutions that are systemically important. The analysis was performed using Panel Data Regression, SVAR, and FEVD on individual bank data and macroeconomic data. The findings proved that government policies to drive the business cycle and MSME actors in the context of overcoming the impact of Covid-19, have not shown their effectiveness. This is indicated by the negative response of economic growth to the policies that have been issued. On the other hand, the performance of banking financial institutions also contributes to national economic growth. This is indicated by the sensitivity of the bank's internal variables in responding to national economic growth. Likewise, with the response to government policies and macroeconomic conditions. Therefore, there is a need for an acceleration policy in handling the current national economic recovery.Originality/Value: This paper focus on systematic risk in banking during COVID-19, use of advanced econometric techniques, evaluation of government policies, integration of bank performance and macroeconomic growth, and its assessment of policy effectiveness, and its implications for future economic recovery efforts.